(untitled) (Revista Latinoamericana de Derechos Humanos, 2010)
Resumen En este artículo se presentan comparativamente los resultados de dos encuestas realizadas en los años 1999 y 2008, a muestras aleatorias de estudiantes de la UNA. El objetivo de estas era conocer la prevalencia3 del hostigamiento sexual, durante su permanencia en la Universidad Nacional. También se comparan las manifestaciones y los efectos de esta forma de violencia y se analiza el impacto de la Campaña de Prevención 2007 que tuvo como lema “Cero Tolerancia al Hostigamiento Sexual”. Abstract This article presents the comparative results of two surveys done in 1999 and 2008, in a random UNA´s students´s sampling. The goal of these was to know the prevalence in students (in terms of man and women percentage) that suffer some manifestations of sexual harassment during the time they stay at the Universidad Nacional. Also, the manifestations and effects of this kind of violence are compared, and it analyses the impact of the “Prevention Campaign 2007” with the slogan “Cero Tolerancia al Hostigamiento Sexual”.